The relationship between vigilance and cortical EEG manifestations after electrical stimulation of the thalamus and hippocampus in unrestrained rats - Kolínová, M; Chocholová, L (Physiologia Bohemoslovaca, 1978)
The thalamus or hippocampus of unanaesthetized rats with impaired cortical and subcortical electrodes was stimulated with rhythmic series of electrical pulses of 3--15/sec frequency. In both cases, stimulation either did not affect vigilance, or led to a higher degree of wakefulness. The incidence of recruiting responses (RR) and of self-sustained afterdischarges (SSAD) evoked by stimulation of the thalamus was not correlated to the preceding state of vigilance. In stimulation of the hippocampus, a significantly higher incidence of SSAD was found in the quiet waking state. The correlation between the elicitation of RR and SSAD was also significantly the highest after stimulation of the hippocampus during wakefulness.
Keywords: recruitment (neurofyziologie); elektrická stimulace; Recruitment, Neurophysiological; krysa rodu Rattus; thalamus; elektroencefalografie; mozková kůra; Hippocampus; Electroencephalography; Thalamus; Wakefulness; Animals; Electric Stimulation; Rats; bdění; zvířata; hipokampus; Cerebral Cortex